Assessment of Thermal Discomfort Variation in Fiji's Major Urban Centers. (3rd April 2022) - Fong, Stephanie; Rana, Rubina; Pratap, Arti; Ongoma, Victor
Abstract: Thermal discomfort and heat stress have become common concerns, especially in an urbanized environment. This work investigates the changes in thermal comfort of Fiji's urban centers. The analysis is based on Thom's discomfort index (DI), calculated from observed temperature and humidity data during 1985–2019. Discomfort is highest in austral summer (November – April) and lowest in winter (June – August). Discomfort increased from the late 1990s to 2000s. Given that the urban centers under this study are still expanding, the level of discomfort is expected to worsen. The observed thermal comfort condition is likely to have an adverse impact on the urban population, especially the elderly people. In addition, a higher DI is likely to affect the country's tourism industry. Proper building designs and increase in the country's vegetation covers are practical and effective measures to manage the discomfort. There remains a need for instantaneous change in DI studies, monitoring its changes using high-resolution datasets, and to assessing the people's actual thermal feeling based on a survey.